Invasive Trichoderma spp. infections: clinical presentation and outcome of cases from the literature and the FungiScope® registry - Sal, Ertan; Stemler, Jannik; Salmanton-García, Jon; Falces-Romero, Iker; Kredics, László; Meyer, Elisabeth; Würstl, Benjamin; Lass-Flörl, Cornelia; Racil, Zdenek; Klimko, Nikolay; Cesaro, Simone; Kindo, Anupma Jyoti; et al. (The Journal of antimicrobial chemotherapy, 2022)
BACKGROUND: Trichoderma spp. are filamentous fungi causing invasive fungal diseases in patients with haematological malignancies and in peritoneal dialysis patients. OBJECTIVES: To analyse clinical presentation, predisposing factors, treatment and outcome of Trichoderma infections. METHODS: A systematic literature review was conducted for published cases of invasive Trichoderma infection in PubMed until December 2021 and by reviewing the included studies' references. Cases from the FungiScope® registry were added to a combined analysis. RESULTS: We identified 50 invasive infections due to Trichoderma species, including 11 in the FungiScope® registry. The main underlying conditions were haematological malignancies in 19 and continuous ambulatory peritoneal dialysis (CAPD) in 10 cases. The most prevalent infection sites were lung (42%) and peritoneum (22%). Systemic antifungal therapy was administered in 42 cases (84%), mostly amphotericin B (n = 27, lipid-based formulation 13/27) and voriconazole in 15 cases (30%). Surgical interventions were performed in 13 cases (26%). Overall mortality was 48% (n = 24) and highest for allogeneic HSCT and solid organ transplantation (SOT) recipients [80% (4/5) and 77% (7/9), respectively]. In patients treated with amphotericin B, voriconazole and caspofungin, mortality was 55% (15/27), 46% (7/15) and 28% (2/7), respectively. Three out of four patients treated with a combination therapy of voriconazole and caspofungin survived. CONCLUSIONS: Despite treatment with antifungal therapies and surgery, invasive Trichoderma infections are life-threatening complications in immunocompromised patients, especially after HSCT and SOT. In addition, Trichoderma spp. mainly affect the lungs in patients with haematological malignancies and the peritoneum in CAPD patients.
Keywords: Hematologic Neoplasms; vorikonazol; Antifungal Agents; antifungální látky; Trichoderma; Registries; kaspofungin; lidé; amfotericin B; hematologické nádory; registrace; Amphotericin B; Voriconazole; Humans; Caspofungin